The Impact of Trade Preferences on Multilateral Tariff Cuts: Evidence for Japan - Tobias Ketterer; Daniel M. Bernhofen; Chris Milner (Center for Economic Studies and ifo Institute (CESifo), 2014)
Opposing theoretical predictions on the effects of trade preferences on multilateral tariff cuts point to the need for empirical analysis to determine whether preferential trade agreements promote or hinder multilateral trade liberalization. This paper examines the impact of Japan's trade preferences on its multi-lateral tariff reductions. Using detailed product level data, we find that Japan's Generalized System of Preferences (GSP) acted as a stumbling block for the country's external tariff liberalization during the Uruguay Round of multi-lateral trade negotiations.
Keywords: F13; F14; 330; Japan's Generalized System of Preferences; Japan's Most Favoured Nation tariffs; Uruguay Round